2015
DOI: 10.12944/cwe.10.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplanktonic Diversity and Its Relation to Physico-chemical Parameters of Water at Dogarwada Ghat of River Narmada

Abstract: Present study was undertaken to assess the spatial and temporal distribution of phytoplanktons with respect to the changes in various physico-chemical parameters of Dongarwada ghat of river Narmada Madhya Pradesh. The study was carried for a year from March 2010 to February 2011.The results revealed presence of total 27 taxa of phytoplanktons belonging to 4 families were found in order of Chlorophyceae (47%) >Cyanophyceae (27%) >Bacillariophyceae (23%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The similar trends of succession such as, Chlorophyceae>Cyanophyceae>Bacillariophy ceae>Euglenophyceae(Fig. 6) in microalgae community were noticed in the earlier studies on the Narmada River basin time to time (Sharma et al, 2011;Sharma et al, 2015). However, different succession with a dominant group as Bacillariophyceae was recorded from the mixed zone of Narmada River (Saini et al, 2015, Rai et al, 2016.…”
Section: Seasonal and Locational Variations In Microalgae Abundancesupporting
confidence: 74%
See 1 more Smart Citation
“…The similar trends of succession such as, Chlorophyceae>Cyanophyceae>Bacillariophy ceae>Euglenophyceae(Fig. 6) in microalgae community were noticed in the earlier studies on the Narmada River basin time to time (Sharma et al, 2011;Sharma et al, 2015). However, different succession with a dominant group as Bacillariophyceae was recorded from the mixed zone of Narmada River (Saini et al, 2015, Rai et al, 2016.…”
Section: Seasonal and Locational Variations In Microalgae Abundancesupporting
confidence: 74%
“…4B). Alkalinity was highest in monsoon and low in winters, but no regular trend was observed with mean values of 136.66± 55.84 in Narmada River at Dograwada Ghat (Sharma et al, 2015). Total hardness varied from 79 -196 mg/l and the highest peak observed in May (196 mg/l) and lowest in July (79 mg/l) in Dograwada Ghat (Sharma et al, 2015).…”
Section: Physical and Chemical Characteristics Of Watermentioning
confidence: 90%
“…Summer is the most suitable season for the growth of phytoplankton in the waterbody because of long duration of sunshine period, increased salinity, and pH. Sharma et al, (2014) also observed that phytoplankton grow and multiply best during summer season when the temperature is high, depends on the nutrients and having longer photoperiod. The annual percentage composition of different groups of phytoplanktons revealed 48.12 % Chlorophyceae followed by 27.81 % Bacillariophyceae, 15.03 % Cyanophyceae and 9.02 % Euglenophyceae.…”
Section: Resultsmentioning
confidence: 98%
“…Plankton samples were obtained in 150ml labeled plastic bottles using plankton net of 55μm mesh size that was slowly hauled horizontally at about 30 cm depth against the water current in each sampling station for 5 minutes. Samples were then preserved in 4% formalin as described by Ogbuagu and Ayoade (2012) and Sharma et al (2015). Samples were obtained during daylight between 11am and 2pm so as to minimize variations as a result of the diurnal migration of plankton (Adesalu, 2012).…”
Section: Sampling Of Phytoplankton and Environmental Variablesmentioning
confidence: 99%
“…Phytoplankton are free-floating unicellular and colonial organisms that form a crucial part of an aquatic ecosystem as they are the primary producers through which energy is transferred to higher organisms in the food chain (Saifullah et al, 2014;Sharma et al, 2015;Tilahun and Ayalew, 2015). They inhabit the upper part of the water column down to the limit of light penetration known as the euphotic zone.…”
Section: Introductionmentioning
confidence: 99%